Exploring deaf student teachers’ academic experiences at a teacher training college in Rwanda - James Maizere (International Journal of Studies in Inclusive Education)
From Eugenics to the institutionalisation period, Deaf students were discriminated against. Their education in African countries is minimal, especially in tertiary institutions, including Rwanda. The study explored the academic experiences of deaf student teachers at a Teacher Training College (TTC) in Rwanda. It used the interpretive paradigm and qualitative research approach. The study employed a narrative case study. The study population comprised two TTC administrators, two deaf student teachers, all the sixteen tutors who taught the deaf student teachers, and two library workers. One TTC administrator, two deaf student teachers, one teacher, and one library worker were purposively sampled, comprising five participants. The study found that the TTC did not have resources to educate deaf student teachers. The study also found that the tutors and the deaf student teachers relied on detailed notes, handouts, and an interpreter. It also found that deaf student teachers preferred Rwandan Sign Language because they had no communication options. The study recommended that the Rwanda Basic Education Board should provide resources for the education of deaf student teachers. Moreover, the Department of Special Needs and Inclusive Education should have a viable Rwandan Sign Language group to educate the hearing TTC community on Rwandan Sign Language.